Use of big data in transport modelling - Luis G. Willumsen (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2021)
This paper guides transport planners in making the best use of mobile phone traces, derived either from mobile network data or from smartphone app data. It suggests combining such new data sources with conventional travel surveys whose sample size and cost could ultimately be reduced. In the context of a rapidly evolving mobility landscape, with new modes and new services available, big data can help monitor behaviour change, learn from quasi-experiments and develop next-generation travel demand modelling tools.
Keywords: 330